2012
DOI: 10.1523/jneurosci.2895-11.2012
|View full text |Cite
|
Sign up to set email alerts
|

The Nucleosome Remodeling and Deacetylase Chromatin Remodeling (NuRD) Complex Is Required for Peripheral Nerve Myelination

Abstract: Several key transcription factors and coregulators important to peripheral nerve myelination have been identified, but the contributions of specific chromatin remodeling complexes to peripheral nerve myelination have not been analyzed. Chromodomain helicase DNA-binding protein 4 (Chd4) is the core catalytic subunit of the Nucleosome Remodeling and Deacetylase (NuRD) chromatin remodeling complex. Previous studies have shown Chd4 interacts with Nab (NGFI-A/Egr-binding) corepressors, which are required for Early … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(64 citation statements)
references
References 61 publications
(121 reference statements)
4
60
0
Order By: Relevance
“…The CHD family member, CHD4, reportedly regulates myelination in the PNS (Hung et al 2012). CHD4 conditional mutant mice show a delay in myelination and an increase of immature Schwann cell proliferation.…”
Section: Atp-dependent Chromatin Remodeling Complexmentioning
confidence: 99%
“…The CHD family member, CHD4, reportedly regulates myelination in the PNS (Hung et al 2012). CHD4 conditional mutant mice show a delay in myelination and an increase of immature Schwann cell proliferation.…”
Section: Atp-dependent Chromatin Remodeling Complexmentioning
confidence: 99%
“…Nab proteins interact among others with the chromodomain helicase DNA-binding protein 4 (Chd4) that is part of the NuRD chromatin-remodeling complex (Srinivasan et al, 2006). Interestingly, Schwann cells in conditional Chd4 mouse mutants are transiently arrested at the promyelinating stage even though Sox10 and Krox20 are expressed (Hung et al, 2012). Nab proteins may thus provide a link between Krox20 and NuRD complex as a further chromatin remodeling complex with functional relevance for Schwann cell differentiation (Fig.…”
Section: Q4mentioning
confidence: 99%
“…We found that Chd5-compromised mice have severe behavioral phenotypes and aberrant dendritic arborization (Mills, unpublished). A de novo mutation in CHD4 was reported in 1/109 patients with epileptic encephalopathy [109], and conditional disruption of Chd4 specifically within Schwann cells leads to abnormal motor co-ordination and hind limb reflexes [116]. While more supporting human genetic data are needed, these functional data in model organisms and preliminary reports in humans suggest that perturbation of CHD4, CHD5 and CHD6 might also play important roles in neurological dysfunction.…”
Section: Chd Proteins In Neurological Syndromesmentioning
confidence: 99%
“…In addtion, Chd4 is essential for polycomb-mediated inhibition of astroglial differentiation through its interaction with Ezh2 and suppression of genes that induce the astrogenic lineage [128]. Chd4 also interacts with Nab corepressors to direct Schwann cell mediated peripheral nerve myelination, and conditional ablation of Chd4 in Schwann cells leads to delayed myelination, radial sorting defects, hypomyelination and deregulation of promyelinating Schwann cells [116]. In addition, Chd4 is required for expression of CD4 (CD4 molecule) and T-cell development [129], and CHD4 forms a complex with GATA3 (GATA-binding protein 3) to simultaneously activate transcription of Th2 cytokines and to repress transcription of the Th1 cytokine IFNG (interferon, γ) to establish T helper 2 cell identity [130].…”
Section: Chd Proteins In Developmental Disordersmentioning
confidence: 99%
See 1 more Smart Citation